The complementary and divergent roles of uncoupling proteins 1 and 3 in thermoregulation. (13th November 2016) - Riley, Christopher L.; Dao, Christine; Kenaston, M. Alexander; Muto, Luigina; Kohno, Shohei; Nowinski, Sara M.; Solmonson, Ashley D.; Pfeiffer, Matthew; Sack, Michael N.; Lu, Zhongping; Fiermonte, Giuseppe; Sprague, Jon E.; et al.
Abstract : Key points: Both uncoupling protein 1 (UCP1) and UCP3 are important for mammalian thermoregulation. UCP1 and UCP3 in brown adipose tissue mediate early and late phases of sympathomimetic thermogenesis, respectively. Lipopolysaccharide thermogenesis requires skeletal muscle UCP3 but not UCP1. Acute noradrenaline‐induced hyperthermia requires UCP1 but not UCP3. Loss of both UCP1 and UCP3 accelerate the loss of body temperature compared to UCP1KO alone during acute cold exposure. Abstract: Uncoupling protein 1 (UCP1) is the established mediator of brown adipose tissue‐dependent thermogenesis. In contrast, the role of UCP3, expressed in both skeletal muscle and brown adipose tissue, in thermoregulatory physiology is less well understood. Here, we show that mice lacking UCP3 (UCP3KO) have impaired sympathomimetic (methamphetamine) and completely abrogated lipopolysaccharide (LPS) thermogenesis, but a normal response to noradrenaline. By comparison, UCP1 knockout (UCP1KO) mice exhibit blunted methamphetamine and fully inhibited noradrenaline thermogenesis, but an increased febrile response to LPS. We further establish that mice lacking both UCP1 and 3 (UCPDK) fail to show methamphetamine‐induced hyperthermia, and have a markedly accelerated loss of body temperature and survival after cold exposure compared to UCP1KO mice. Finally, we show that skeletal muscle‐specific human UCP3 expression is able to significantly rescue LPS, but not sympathomimetic thermogenesis blunted in UCP3KO mice. These studies identify UCP3 as an important mediator of physiological thermogenesis and support a renewed focus on targeting UCP3 in metabolic physiology. Key points: Both uncoupling protein 1 (UCP1) and UCP3 are important for mammalian thermoregulation. UCP1 and UCP3 in brown adipose tissue mediate early and late phases of sympathomimetic thermogenesis, respectively. Lipopolysaccharide thermogenesis requires skeletal muscle UCP3 but not UCP1. Acute noradrenaline‐induced hyperthermia requires UCP1 but not UCP3. Loss of both UCP1 and UCP3 accelerate the loss of body temperature compared to UCP1KO alone during acute cold exposure.